Comparison between predicted and observed settlement of vertical drain treated road embankment on soft clay - Ahmad, Mohd. Redzuan (2006)
Prefabricated Vertical Drain (PVD) with surcharge preloading is one of the most widely used techniques to accelerate the process of consolidation. In practice it is sometime difficult to choose proper design parameters in PVD design. Backanalysis from field records is a good method to verify the design parameters. This study was undertaken to compare the predicted and monitored settlement of a road embankment on soft clay treated with PVD. Back-calculation of the design parameters was performed based on the available monitoring records. Magnitude of settlement was calculated using the classical one-dimensional consolidation theory. The monitored settlement was then evaluated using Asaoka’s method. Terzaghi- Hansbo’s solution was adopted in predicting the time-rate of consolidation with the application of PVD. The analysis and comparison between field and laboratory (or theoretical) value of the settlement design parameters show that the coefficient of volume compressibility mvlab=1.25mvfield, compression ratio CRlab=1.19CRfield, and the ratio of coefficient of horizontal to the vertical consolidation ch/cv= 1.6. ch from piezocone dissipation test was found to be 3 times larger than the back-calculated ch value. The study also suggests that smear effect is a factor which cannot be ignored in the design of PVD